(13)C/(31)P NMR studies of glucose transport in human skeletal muscle - Roussel, Ronan (The National Academy of Sciences, 1998)
The muscle intracellular (IC) free glucose concentration and the rate of muscle glycogen synthesis were measured by using in vivo (13)C and (31)P NMR spectroscopy in normal volunteers under hyperinsulinemic (≈300 pM) clamp conditions at the following three plasma glucose levels: euglycemia (≈6 mM), mild (≈10 mM), and high (≈16 mM) hyperglycemia. In keeping with biopsy studies, muscle IC free glucose concentration at euglycemia (−0.03 ± 0.03 mmol/kg of muscle, mean ± SEM, n = 10) was not statistically different from zero. A small but statistically significant amount of IC free glucose was observed during mild and high hyperglycemia: 0.15 ± 0.08 (n = 5) and 0.43 ± 0.20 mmol/kg of muscle (n = 5), respectively. Muscle glycogen synthesis rate, in mmol per kg of muscle per min, was 111 ± 11 at euglycemia (n = 10), 263 ± 29 during mild hyperglycemia (n = 5), and 338 ± 42 during high hyperglycemia (n = 5), these three rates being significantly different from each other. As previous in vitro and in vivo studies, these rates suggest a K(m) (concentration at which unidirectional glucose transport reaches half-maximal rate) of the muscle glucose transport system in the 15–25 mM range under hyperinsulinemic conditions. The low concentrations of muscle IC free glucose observed under hyperinsulinemic conditions were interpreted, with this estimate and in the framework of metabolic control theory, as glucose transport being the predominant step controlling muscle glucose flux not only at euglycemia but also during hyperglycemia.